Pengaruh Penambahan Fraksi Berat Zirconia terhadap Sifat Fisik dan Mekanik Komposit Aluminium Diperkuat Zirconia yang Diproduksi dengan Metalurgi Serbuk - Wardhana, Bayu Satriya (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2014)
This research aims to utilize zirconia (ZrO ) as a reinforcement of aluminum matrix composite (AMC). ZrO 2 2 powder of 0%, 2.5%, 5%, 7.5%, 10%, 12,5%, and 15% wt were added to fine aluminum powder (dimension of particles are smaller than 40 Î¼m). Each composition was mixed using a turbula mixer for 2 hr. The mixture was uniaxially pressed with a pressure of 300 MPa to produce green bodies. They were pressure less sintered in argon atmosphere at temperature of 600ÂºC. Relative density, Vickers hardness, and bending strength of the AMC were tested. The results show that the hardness increases with increasing the ZrO content up to 5% wt whereas wear rate decrease. Relative density and Vickers hardness of composite containing 5% ZrO2 are 89%, 34 HV15 and 0.076 mg/(MPa.m), respectively. Maximum bending strength was reach on 7,5% ZrO adding on 37,66 MPa.Keyword : Aluminum Matrix Composite, zirconia, uniaxial compaction 2 2